Do online reviews always incentivise remanufacturers to improve quality in a competitive environment? - Shushu Xie; Yingxue Zhao; Lin Zhao; Xingyuan He (Amfiteatru Economic, 2024)
Consumers underestimation of the quality of remanufactured products is a barrier for remanufacturers. Online reviews provide quality signals to consumers unaware of remanufactured products. To explore whether remanufacturers produce higher quality products to improve their review ratings, considering the quality signalling effect of online reviews, a closed-loop supply chain model of the original equipment manufacturer (OEM) and independent remanufacturer (IR) was developed. The IR's two strategies, with and without online reviews, were compared to analyse the quality signalling effect of online reviews on the IR's production, pricing, and quality decisions. The results show that when the IR chooses full remanufacturing, online reviews have a quality-enhancing effect on the remanufactured product if the variable investment coefficient of the quality improvement effort is low. However, if an IR chooses partial remanufacturing, then online reviews do not have a quality-enhancing effect on the remanufactured product. In addition, if the impact of online reviews on consumers' willingness to pay for remanufactured products is negative, then the IR does not improve quality. The conclusions obtained from this study provide managerial implications for selecting quality strategies and implementing operational decisions for remanufacturers entering the e-commerce channel.
Keywords: C70; D21; D24; D40; L11; 330; closed-loop supply chain; game theory; Online reviews; quality; quality signalling effect; remanufacturing